Digitizing the veterinary formulary - Hennedige, Kalana Manika (Nanyang Technological University, 2023)
Veterinary medicine has made rapid strides in diagnosing and treating patients, with advances in drug development enabling veterinarians to diagnose and treat a variety of illnesses more effectively. More precise and specialised drugs have allowed for better targeting of treatments and more accurate dosing. However, little attention has been given to software catered to the veterinary field, more specifically to building and using databases for veterinary drugs; evidence of this would be the fact that manual calculation of drug doses is still commonplace in many veterinary practices. Manual calculation subjects these final doses to the risk of human error, increasing the likelihood of mistakes or inconsistencies in dosage.